The great retrenchment: International capital flows during the global financial crisis - Gian-Maria Milesi-Ferretti; Cédric Tille (Graduate Institute of International and Development Studies, 2010)
The current crisis saw an unprecedented collapse in international capital flows after years of rising financial globalization. We identify the stylized facts and main drivers of this development. The retrenchment in international capital flows is a highly heterogeneous phenomenon: first across time, being especially dramatic in the wake of the Lehman Brothers' failure, second across types of flows, with banking flows being the hardest hit due to their sensitivity of risk perception, and third across regions, with emerging economies experiencing a shorter-lived retrenchment than developed economies. Our econometric analysis shows that the magnitude of the retrenchment in capital flows across countries is linked to the extent of international financial integration, its specific nature - with countries relying on bank flows being the hardest hit - as well as domestic macroeconomic conditions and their connection to world trade flows.
Keywords: 330; Kapitalmobilität; Finanzmarktregulierung; Finanzkrise; Welt